Earnings persistence of Nigerian listed banks - Segun Abogun; Taiwo Azeez Olaniyi; Muftau Adeniyi Ijaiya; Temitope Olamide Fagbemi (Jurnal Siasat Bisnis, 2020)
Banks report huge profits yearly yet some of these banks were reported to lack capital adequacy and some were reported to be close to being insolvent. Therefore, it is important to determine whether or not the profits reported by these banks are persistent. As a result, the main objective of this study is to examine the persistence of earnings of Nigerian listed banks. The explanatory research design was adopted and data were gathered from the secondary source, specifically from the financial statements of Nigerian quoted banks. The entire fifteen (15) quoted deposit money banks which constitute the population of the study was examined over a period of eleven (11) years spanning 2005 to 2015. In this study, the Generalized Method of Moments (GMM) dynamic panel estimation technique was employed. The study found that the earnings of the Nigerian listed banks are less persistent, that is, less sustainable. It is therefore recommended that investors should exercise caution by paying less attention to reported earnings. Instead, effort should be made to determine the persistent level of earnings to avoid wrong investment decisions.